Nutrition‐related interventions targeting childhood overweight and obesity: A narrative review. (16th August 2019) - Kerr, Jessica A.; Loughman, Amy; Knox, Andrew; Koplin, Jennifer J.; Allen, Katrina J.; Wake, Melissa
Summary: Systematic reviews of nutritional interventions indicate limited efficacy in reducing childhood obesity, but their blanket conclusions could obscure promising components. This narrative review sought more detail on effective components within nutrition‐related interventions involving children aged 2 to 11 years. In May 2016, the World Health Organization (WHO) searched the Cochrane Library and PubMed for relevant reviews. From 36 reviews, we screened 182 nutrition‐related randomized trials for inclusion. We then reviewed those that reported at least 1 statistically significant ( P  < 0.05) treatment benefit on body weight and/or composition outcomes at their longest follow‐up assessment. Fourteen trials met inclusion criteria (median n = 554; mean intervention duration = 10.8 mo; follow‐up = 4.4 mo). "Effective" approaches included environmental changes such as school water fountain installations and cafeteria menu changes and possibly less sustainable strategies such as health education lessons. However, effect sizes even of these selected significant treatment benefits were modest—significant body mass index z‐score effects range from −0.1 to −0.2. Each trial was associated with very small improvements in body composition. Because this is a "best‐case" scenario (reflecting our design), trialists should rigorously test these strategies alone and possibly together; be open to novel strategies; and ensure that each strategy is culturally relevant and self‐sustainable.